A Shariah compliant private equity fund : compatibility in South Africa - Cajee, Mohsin Ebrahim (Department of Finance and Tax, 2016)
There is no doubt that the equity market plays a central role in the growth and the sustainability of an economy. Equity and capital markets allow companies to access increased levels of accessibility to capital. Besides the traditional models to access for corporate finance, new opportunities have appeared which offer interesting alternatives. The accumulated wealth from the Islamic community became accessible through new vehicles, built on the Islamic Shariah laws in as far as money and banking is concerned. The Islamic concepts of money and banking, emphasise the relationship between profit and risk as well as responsibilities of institutions and individuals. Many of the guiding principles of corporate finance and banking would not be pegged on religious provisions and doctrines. The Western, conventional economic system holds opposing views to Islamic economics and a key question arises, could principles of Islamic finance feed into a Western economic system and be maintained on a sustainable basis? Proponents and supporters of a Shariah compliant economic system argue that religion is meant to affect every other aspect of life and so would be the economic principles one stands for. As such, remaining committed and observing Islamic law in business and economic activities would be inevitable for all those who take pride in prophesying the Islamic faith. More recently, regulators in South Africa have taken a number of steps to promote Islamic finance in South Africa. The country has one of the more efficient and advanced financial systems, legal and tax frameworks as well as governance structures and regulations on the continent. This gives South Africa a competitive edge and first mover advantage over other African countries in promoting and advancing the Islamic finance industry. The main goal of this mini thesis is the study of what constitutes an Islamic Shariah compliant Private Equity Fund (IPEF). At a secondary and more basic level its viability is considered within a South African context. It also examines the key challenges and potential solutions for such a fund to exist in an economy based largely on Western principles, particularly with reference to the legal frameworks, interest treatment, taxation laws, regulatory and supervisory bodies as well as basic conceptual understandings. Of great attention to the researcher would be the differences between the conventional economic principles that guide equity and finance in South Africa and how Shariah compliance has affected the trade instruments. The author of this thesis has vast experience in the area of Private Equity and Islamic finance as it pertains to this field. In this work, the author builds on his own experience and critically reflects it against the dominant literature in the field. This work does not focus on the risk/return profile or provide any consideration as to the likely performance of such Islamic Private Equity Funds.